Large‐eddy simulation of downhole flow: The effects of flow and rotation rates. (19th March 2021) - Borges, Jonatas Emmanuel; Padilla, Elie Luis Martínez; Lourenço, Marcos Antonio Souza; Micallef, Christopher
Abstract: The present paper concerns large‐eddy simulations of turbulent downhole flow for six Reynolds numbers and five Taylor numbers. Swirl parameter within the range (0‐0.98), which compares the effects of the rotation and the flow rates, was evaluated. In this work, the fluid is injected through the drill pipe and then accelerated by the nozzle. As the fluid discharges from the nozzle, a high speed jet is generated in the downhole region, the fluid then impinges the bottomhole surface and finally flows out the downhole region through the annulus. The nozzle is represented by a sudden contraction. The dynamic sub‐grid scale model has been used to calculate the turbulent viscosity. The immersed boundary method is employed to represent the solid walls of the proposed geometry. Coherent structures appear as spiral rolls into the nozzle and their inclination angles depend on the rotational speed. When the rotational speed increases, these structures are more aligned with the tangential direction. Due to the geometry of the problem, a toroidal vortex takes place and it grows as the Reynolds number increases. The magnitude of the velocity fluctuations increase in the jet region and near the sidewall with increasing flow rate; it also increased in the jet region with increasing rotational speeds. The impact force and the peak pressure on the impacted surface increases with increasing flow rates. Good agreement of the impact force with other works supports the present work methodology.